Role of abiotic drivers on crab burrow distribution in a saltmarsh wetland - Chen, Xue; Zhou, Zeng; He, Qiang; Zhang, Heyue; Bouma, Tjeerd; Gong, Zheng; Townend, Ian; Zhang, Changkuan (Frontiers in Marine Science, 2022)
Crab burrows play an important role in saltmarsh wetlands and are a useful indicator of wetland condition. The spatiotemporal distribution of crab burrows varies considerably in tidal wetlands. However, the reasons for these variations are poorly understood, in part, due to the limited availability of comprehensive field data. Based on a two-year continuous observation at a tidal wetland in the northern Jiangsu Coast, China, this study explored the relationship between crab burrow density and environmental variables, including median grain size, water content, organic matter content, soil salinity, and elevation. Our results show that the distribution of crab burrows was unimodal across the shore in winter and spring (Nov-Apr) when air temperature was relatively low, while bimodal in summer and autumn (May-Oct) when temperature was relatively high. The density of crab burrows was larger at areas with higher water content, higher organic matter content, and lower soil salinity, while it was lower with stronger hydrodynamics and lower suspended sediment concentration. Crab burrows were more abundant in vegetated areas than in un-vegetated areas. A backward stepwise model selection was performed based on R-square and Akaike information criterion (AIC) to distinguish the main driving factors that determine crab burrow distribution. Results suggested that the principal driving factors were organic matter content and soil salinity in all the seasons, with the addition of water content in warm seasons. Overall, this study provides a comprehensive field dataset for a more in-depth understanding of crab burrow distribution and a scientific basis for sustainable management of tidal wetlands.